Ketahanan Bank Umum Syariah di Indonesia Terhadap Fluktuasi Makroekonomi dalam Negeri dan Suku Bunga Dana Federal Reserve - Donna Sita Soraya Kristanti Jatmiko; Djoni Djatnika; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The development of banking in a country cannot be separated from internal and external factors that can influence it. The monetary crisis in 1998 and the global financial crisis in 2008 are some examples that show that the banking sector can be affected by the surrounding economic conditions, both from within and outside the country. The purpose of this study is to determine the resilience of Islamic commercial banks in Indonesia if there are shocks that occur in macroeconomics, in this case, namely inflation, exchange rates, Bank Indonesia benchmark interest rate (BI rate), SBIS yields (rSBIS) and Federal Reserve funds interest rates. (FFR). This study uses the Vector Autoregression (VAR) and Vector Error Correction Model (VECM) methods. The conclusion of this study is that Non-Performing Financing (NPF) and Return on Assets (ROA) in Islamic commercial banks in Indonesia tend to be more resistant to fluctuations that occur in domestic macroeconomics and FFR. The Capital Adequacy Ratio (CAR) is relatively stable in responding to a shock, while the Return on Equity (ROE) and Financing Deposit Ratio (FDR) have fluctuated in the long term in other words, they are more vulnerable to shocks and fluctuations that occur in domestic macroeconomic variables and FFR.